The Influence of Use of Technology, Flexitime, and Tele Working on Employee Performance with Work-Life Balance as a Mediating Variable - Catherine Liana Suhandi; Kurnadi Gularso (Journal of Social Science, 2024)
This study aims to examine the influence of Use Of Technology, Flexitime, and Tele Working on the performance of Generation Z employees in the Tangerang and Jakarta areas, with work-life balance as a mediating variable. Adopting a quantitative approach, this study used questionnaires distributed to Gen Z employees from various industrial sectors. Data analysis was conducted using regression techniques and mediation analysis. The results showed that Use Of Technology, Flexitime, and Tele Working significantly contributed to the performance of Gen Z employees in the region. In addition, work-life balance was shown to mediate the relationship between these factors and Gen Z employee performance. These findings provide important insights for organizations and HR managers in designing policies and strategies that suit the preferences and needs of the younger generation in a rapidly changing work environment. This research also has the potential to contribute to the literature on human resource management, especially in the context of youth work and Use of Technology